Taking patients' wishes into account for daily planning in the Home Health Care contex. Issue 11 (2018) - Mascolo, M. Di; Espinouse, M.L.; Haddadene, S.R. Ait
Abstract: We consider here the daily planning of human resources for home health care. We give a mathematical formulation of the problem, as a mixed integer linear program integrating real-world constraints, such as disjunction, synchronization and precedence between tasks. Our objective is to optimize several indicators of patients' satisfaction, regarding time of care and the caregivers' gender. We assess the performance of the MILP with some data generated in order to fit the specificities of the practical problem.